Ensuring Nutritious Food Under Elevated CO2 Conditions: A Case for Improved C4 Crops - Jobe, Timothy O.; Rahimzadeh Karvansara, Parisa; Zenzen, Ivan; Kopriva, Stanislav (Frontiers in Plant Science, 2020)
Global climate change is a challenge for efforts to ensure food security for future generations. It will affect crop yields through changes in temperature and precipitation, as well as the nutritional quality of crops. Increased atmospheric CO2 leads to a penalty in the content of proteins and micronutrients in most staple crops, with the possible exception of C4 crops. It is essential to understand the control of nutrient homeostasis to mitigate this penalty. However, despite the importance of mineral nutrition for plant performance, comparably less is known about the regulation of nutrient uptake and homeostasis in C4 plants than in C3 plants and mineral nutrition has not been a strong focus of the C4 research. Here we review what is known about C4 specific features of nitrogen and sulfur assimilation as well as of homeostasis of other essential elements. We identify the major knowledge gaps and urgent questions for future research. We argue that adaptations in mineral nutrition were an integral part of the evolution of C4 photosynthesis and should be considered in the attempts to engineer C4 photosynthetic mechanisms into C3 crops.